Internal quality assurance in a clinical virology laboratory. II. Internal quality control. Issue 3 (March 1995) - Gray, J J; Wreghitt, T G; McKee, T A; McIntyre, P; Roth, C E; Smith, D J; Sutehall, G; Higgins, G; Geraghty, R; Whetstone, R
Abstract : AIMS–In April 1991 additional quality control procedures were introduced into the virology section of the Clinical Microbiology and Public Health Laboratory, Cambridge. Internal quality control (IQC) samples were gradually included in the serological assays performed in the laboratory and supplemented kit controls and standard sera. METHODS–From April 1991 to December 1993, 2421 IQC procedures were carried out with reference sera. RESULTS–The IQC samples were evaluated according to the Westgard rules. Violations were recorded in 60 of 1808 (3.3%) controls and were highest in the IQC samples of complement fixation tests (25/312 (8%) of controls submitted for complement fixation tests). CONCLUSIONS–The inclusion of IQC samples in the serological assays performed in the laboratory has highlighted batch to batch variation in commercial assays. The setting of acceptable limits for the IQC samples has increased confidence in the validity of assay results.